Implementation Of Digital Branding For Rural Tourism Development - Putri Ayu Hidayatur Rafiqoh; Widyakanti Widyakanti (Metacommunication: Journal of Communication Studies, 2025)
Rural tourism is a strategic step developed by the government to promote regional culture and improve the global economy. the development of rural tourism can be done through social media by promoting the concept of digital branding, but the fact is that the concept of digital branding is still rarely practiced by rural tourism actors. This research uses exploratory qualitative methods that aim to explore something new, which is not widely known by the public. It is found that to build digital branding, the actors need to pay attention to the keywords, captions and taglines used, identify the uniqueness of the tourist attraction to be featured in the content, and conceptualize the content material about telling experience. By applying these concepts, each destination can promote its uniqueness and characteristics through a digital media effectively.